Acquisition vs. internal development as modes of market entry - Lee, Gwendolyn K.; Lieberman, Marvin B. (Strategic Management Journal, 2009)
Abstract An established firm can enter a new product market through acquisition or internal development. Predictions that the choice of market entry mode depends on ‘relatedness’ between the new product and the firm's existing products have repeatedly failed to gain empirical support. We resolve ambiguity in prior work by developing dynamic measures of relatedness, and by making a distinction between entries inside vs. outside a firm's primary business domain. Using a fine‐grained dataset on the telecommunications sector, we find that inside a firm's primary business domain, acquisitions are used to fill persistent gaps near the firm's existing products, whereas outside that domain, acquisitions are used to extend the enterprise in new directions. Copyright © 2009 John Wiley & Sons, Ltd.